2015
DOI: 10.1093/tropej/fmv018
|View full text |Cite
|
Sign up to set email alerts
|

Human milk banking and milk kinship: Perspectives of mothers in a Muslim country

Abstract: This is the first study conducted among mothers in a Muslim community about issues such as infant feeding, breast milk, wet-nursing, milk kinship and HMBs. The majority of the mothers in this study are against the establishment of Western-style HMBs, whereas they have a more positive response to an alternative HMB when their religious concerns are relieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 13 publications
9
58
2
8
Order By: Relevance
“…Similarly, another current hospital study from Turkey reported that 8.2% of the participants wet nursed a baby and 10.9 % were wet-nursing (12). Wet-nursing numbers were also low in the studies that were done in the city centers in Turkey, which is similar to our study (5,8,13).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, another current hospital study from Turkey reported that 8.2% of the participants wet nursed a baby and 10.9 % were wet-nursing (12). Wet-nursing numbers were also low in the studies that were done in the city centers in Turkey, which is similar to our study (5,8,13).…”
Section: Discussionsupporting
confidence: 90%
“…Currently, there are no active HMBs in Turkey. The Turkish Ministry of Health launched the HMB establishment project in 2012 (8).…”
Section: Introductionmentioning
confidence: 99%
“…Different cultures and religions have different perspectives on the issue of human milk sharing; therefore, cultural and religious beliefs should be implied regarding milk donation (Gürol et al, 2014). Wet-nursing has been widely acceptable in many cultures; however, in the Muslim society anonymised donor is not acceptable, due to the religious belief that the recipient infant would be considered to be the donor's child (Karadag, Ozdemir, Muharrem et al, 2015).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Turkish religious officers have stated that they would only approve the establishment of an alternative human milk bank in which milk would be pooled from a maximum of three donors and up to three recipients, whose identities are known by one another, would be allowed to use donor milk from each milk pool [8,9]. The various religious, cultural, biological, and epigenetic aspects exposed by this study and the uniqueness of the characteristics of human milk support human milk donation by Muslim mothers and Muslim children to receive DHM [10].…”
Section: Discussionmentioning
confidence: 99%